Parental Practices, Healthy Eating and Objective Measures of Body Composition in Preschool Children - Rodríguez Arauz, Gloriana (2017)
This paper describes empirical evidence regarding the relationship between parental practices, healthy eating and objective measures of body composition in preschool children in European, American and Latin American contexts. Concordances are noted in terms of pressure and restriction to eat. Directions are proposed for the development of lines of research in the Latin American context: a) conducting more studies in order to confirm if the relations between the variables of interest are maintained or changed; b) conduct these studies with randomized and representative samples, with self-report and observational measures of parental feeding practices; c) exploration of mediator and moderator roles that cultural and social variables specific to the Latin American context have on the relationships between the variables of interest.